Predictors of In-Hospital Mortality for Stroke in Douala, Cameroon - Mapoure, N. Y. (Hindawi Publishing Corporation, 2014)
Background. The objective of this study was to describe complications in hospitalized patients for stroke and to determine the predictive factors of intrahospital mortality from stroke at the Douala General Hospital (DGH) in Cameroon. Patients and Methods. A prospective cross-sectional study was carried out from January 1, 2010 to December 31, 2012, at the DGH. All the patients who were aged more than 15 years with established diagnosis of stroke were included. A univariate analysis was done to look for factors associated with the risk of death, whilst the predictive factors of death were determined in a multivariate analysis following Cox regression model. Results. Of the 325 patients included patients, 68.1% were males and the mean age was 58.66 ± 13.6 years. Ischaemic stroke accounted for 52% of the cases. Sepsis was the leading complications present in 99 (30.12%) cases. Independent predicting factors of in-hospital mortality were Glasgow Coma Scale lower than 8 (HR = 2.17 95% CI 4.86–36.8; P = 0.0001), hyperglycaemia at admission (HR = 3.61 95% CI 1.38–9.44; P = 0.009), and hemorrhagic stroke (HR = 5.65 95% CI 1.77–18; P = 0.003). Conclusion. The clinician should systematically diagnose and treat infectious states and hyperglycaemia in stroke.